Decolorisation of Reactive Red 120 Dye by Using Single-Walled Carbon Nanotubes in Aqueous Solutions - Edris Bazrafshan; Ferdos Kord Mostafapour; Ali Reza Hosseini; Ataolah Raksh Khorshid; Amir Hossein Mahvi (Journal of Chemistry)
Dyes are one of the most hazardous chemical compound classes found in industrial effluents and need to be treated since their presence in water bodies reduces light penetration, precluding the photosynthesis of aqueous flora. In the present study, single-walled carbon nanotubes (SWCNTs) was used as an adsorbent for the successful removal of Reactive Red 120 (RR-120) textile dye from aqueous solutions. The effect of various operating parameters such as initial concentration of dye, contact time, adsorbent dosage and initial pH was investigated in order to find the optimum adsorption conditions. Equilibrium isotherms were used to identify the possible mechanism of the adsorption process. The optimum pH for removing of RR-120 dye from aqueous solutions was found to be 5 and for this condition maximum predicted adsorption capacity for RR-120 dye was obtained as 426.49 mg/g. Also, the equilibrium data were also fitted to the Langmuir, Freundlich and BET equilibrium isotherm models. It was found that the data fitted to BET (R2=0.9897) better than Langmuir (R2=0.9190) and Freundlich (R2=0.8819) model. Finally it was concluded that the single-walled carbon nanotubes can be used for dye removal from aqueous solutions.